Volunteerism: expanding the frontiers of youth development - Suandi, Turiman (Universiti Putra Malaysia Press, 2009)

(untitled)
The role of young volunteers in improving the quality of life of individuals and of the community is well recognized in Malaysia and other parts of the world. They are active participants in various non-governmental organizations, youth organizations, schools, colleges, universities and even homes for the elderly and orphans, as well as other social welfare centers. Volunteers act as a resource of help and support for individuals, families, services, and institutions. Through volunteering, these young people enter into various social environments and encounter people living in different social circumstances.Through addressing the needs of communities, groups and individuals, volunteering prepares youth towards developing pro-social behaviors in their journey towards adulthood. Through encountering diverse situations involving families, individuals develop tolerance and respect for differences. Thus, youth volunteering is one of the means to nurture the spirit of responsible citizenship. Volunteering motivates young people to continue to get involved in community-oriented volunteer activities even when they become adults. The combination of action and reflection in youth volunteer programs increases the socializing impact of voluntary work. Interestingly, the concepts and practices of youth volunteerism are highly relevant for national stability and community betterment in Malaysia. Stability in Malaysia depends mainly on the attitudes and behavior of its people. Mutual tolerance based on ethnicity, culture and religion and respect for human rights, coexistence, and solidarity are values and behavior patterns that could be enhanced through educating the young people on volunteerism. Thus, developing the spirit of volunteerism is a powerful means to expand the frontiers of youth development. Volunteerism has been and will always be one of the pillars for positive youth development in Malaysia and ultimately, the prosperity of our beloved country. This inaugural paper aims to further redefine the roles of volunteerism as one of the instruments supporting positive youth development.